2018
DOI: 10.1177/0954407018786147
|View full text |Cite
|
Sign up to set email alerts
|

Ageing simulation of a hydraulic engine mount: A data-informed finite element approach

Abstract: Hydraulic engine mounts are key elements in an automotive vehicle suspension system that typically experience a change of their designed function during their working lifetime due to progressive material ageing, primarily from the elastomeric component. Ageing of the engine mount, resulting from severe and continuous mechanical and thermal loads, can have a detrimental impact on the ride and comfort and long-term customer satisfaction. This paper introduces a new practical methodology for simulating the ageing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Specifically, the design of these mounts was based on the lever arm model of the Dynamic Anti-resonant Vibration Isolator (DAVI) concept, first patented in 1967 by Flannelly [31], which is also an inerter. More recent studies of the application of these mounts can be found in [32]- [34]. Devices that exploit relative acceleration to produce inertial force for civil engineering applications were also being developed as modifications to viscous dampers in the late 1990ssee the tuned viscous mass damper (TVMD) described in [35] and references therein.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the design of these mounts was based on the lever arm model of the Dynamic Anti-resonant Vibration Isolator (DAVI) concept, first patented in 1967 by Flannelly [31], which is also an inerter. More recent studies of the application of these mounts can be found in [32]- [34]. Devices that exploit relative acceleration to produce inertial force for civil engineering applications were also being developed as modifications to viscous dampers in the late 1990ssee the tuned viscous mass damper (TVMD) described in [35] and references therein.…”
Section: Introductionmentioning
confidence: 99%
“…It is sensitive to temperature [1] hence the life span and performance of an engine mount affected by different temperatures acting on it. However, the change in mounting criteria is highly contributed by the elastomeric component inside the mount [2]. Therefore, understanding the effect of materials structure on the thermal ageing behavior is crucial for engineers and designers to improve the system.…”
Section: Introductionmentioning
confidence: 99%
“…There are numerous number of studies carried out to improve the properties of engine mounting to isolate the engine vibration, optimizing the engine performance, extending the engine's life span and saving power consumption [2,[5][6]. Our previous studies on GNPs reinforced NR/EPDM blends proven to increase the heat dissipation [4] and improve vibration damping [7]; reflecting their potential to be used in the engine mounting.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond its direct application, the DAVI concept was also used to schematically represent the inertial effect of the first fluid inerter design. This fluid inerter was incorporated into automotive engine mounts [7], where the DAVI lever arm model was used to approximate the effect of a rotating annulus of fluid (called the inertia track) inside the mount -see also [8][9][10]. In addition to this, applications of inerter-like devices in civil engineering evolved from modifications to viscous dampers, that date back to the late 1990s, and eventually resulted in tuned-viscous-mass-dampers -see the discussion in [11] and references therein.…”
Section: Introductionmentioning
confidence: 99%